2019
DOI: 10.1515/psych-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Prototype stories of life with Chemical Intolerance – when the environment becomes a threat to health and well-being

Abstract: We aimed to explore how individuals living with Chemical Intolerance (CI) describe the onset and progression of CI, and how they live and cope with CI. The participants were recruited via Swedish websites hosted by CI support groups. A postal survey, including a Life history calender, was sent to potential participants. Eleven respondents fitted the consensus-based criteria for CI while not reporting comorbidity. A narrative analysis of their written replies resulted in five prototypical stories based on simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…reported symptoms during the last 3 months) and chemical sensitivity (e.g. CSS, Table 1 ) indicated that this group was more affected by their condition than the group with only BRS, which implies a generalized and more severe condition, possibly developed over time as suggested in previous studies 8 , 11 , 45 . We therefore performed separate analyses for these three groups (Referents/BRS/BRS + CI) with the assumption that the combined group (BRS + CI) would react more strongly to the acrolein exposure than the other groups.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…reported symptoms during the last 3 months) and chemical sensitivity (e.g. CSS, Table 1 ) indicated that this group was more affected by their condition than the group with only BRS, which implies a generalized and more severe condition, possibly developed over time as suggested in previous studies 8 , 11 , 45 . We therefore performed separate analyses for these three groups (Referents/BRS/BRS + CI) with the assumption that the combined group (BRS + CI) would react more strongly to the acrolein exposure than the other groups.…”
Section: Discussionsupporting
confidence: 61%
“…Examples of chemical exposure that elicit symptoms among CI cases are exposure to perfumes, cleaning agents, and printing ink. Narratives of individuals experiencing symptoms from residing in buildings with indoor air problems tell that health improvement is initially experienced when the afflicted individuals leave the building in which symptoms have commenced 8 . However, soon enough these individuals experience hypersensitivity to a wide range of everyday chemicals as well as symptoms when residing in other specific buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a former longitudinal study concluded that individuals with BRS had an increased risk of developing burnout at follow-up 36 . Other studies indicate that, over time, some individuals develop a more severe condition 54–56 . An interpretation of the results from this study in light of such former studies could indicate that the mild and moderate group are at risk, over time, of developing a more severe condition, which could include the development of burnout and sleep problems.…”
Section: Discussionsupporting
confidence: 59%
“…36 Other studies indicate that, over time, some individuals develop a more severe condition. [54][55][56] An interpretation of the results from this study in light of such former studies could indicate that the mild and moderate group are at risk, over time, of developing a more severe condition, which could include the development of burnout and sleep problems. We need more knowledge about the role of stress, burnout, and sleep in the development of BRS to understand the complex interaction between the development of symptoms in certain buildings and perception of stress (acute and chronic).…”
Section: Discussionmentioning
confidence: 57%